Acoustics for Engineers – Troy Lectures - DOBRUCKI, Andrzej (Archives of Acoustics, 2012)
Jens Blauert, Ning Xiang, Acoustics for Engineers – Troy LecturesSecond Edition, Springer-Verlag, Berlin Heidelberg, 2009